Patient-centred Preferences for Biologic Therapies in Moderate to Severe Psoriasis in Vietnam: A Discrete Choice Experiment - Chuyen Thi Hong Nguyen; Xuan Thi Mai Nguyen; Trung The Van (Acta Dermato-Venereologica)
Psoriasis is a chronic autoimmune disease that significantly impairs patients’ quality of life. With the growing availability of biologic drugs – each varying in efficacy, safety, dosing, and cost – treatment decisions have become increasingly complex. A study conducted from March to July 2024 surveyed 302 Vietnamese patients with moderate to severe psoriasis to assess preferences for biologic therapies. Using a discrete choice experiment (DCE), participants evaluated 6 treatment attributes: short-term efficacy, long-term efficacy, sustained efficacy after drug withdrawal, frequency of administration, copayment, and risk of serious infection. Preference data were analysed using conditional logit models. Analysis revealed that treatment cost (relative importance [RI]: 31.4%) and long-term efficacy (RI: 25.3%) were the most critical factors influencing patient decisions, while sustained efficacy after withdrawal and early onset of efficacy were less impactful. Long-term efficacy and cost consistently ranked highest across all patient subgroups, with variations depending on demographic and clinical characteristics. These findings provide practical guidance for clinicians to incorporate patient preferences into the selection of biologic therapies, with particular emphasis on treatment cost and long-term efficacy. The significant influence of treatment cost also highlights the need for healthcare policymakers in Vietnam to enhance reimbursement policies and financial support programmes, improving access and equity in psoriasis care.